The Influence of Leadership and Organizational Culture on Employee Performance at PT Lippo General Insurance - Nadzif Al Ghiza (Maneggio, 2024)
Field observations show that the performance of employees at the company PT. LIPPO General Insurance needs to improve and optimize. This can be seen from the low level of employee commitment which can be seen from a lack of sense of responsibility in completing work tasks and responsibilities. Some employees were also found not to be punctual which affected funding at the PT company. LIPPO General Insurance. The research carried out aims to determine the influence that leadership and organizational culture have on the performance of PT Lippo employeesGeneral Insurance. The research is in the quantitative category with multiple linear regression analysis. The results of the research show that leadership has a positive and partially significant influence on employee performance as evidenced by Tcount 2.991 > 2.021 Ttable and significance 0.005 < 0.05. Organizational culture influences employee performance positively and partially significantly based on the results of Tcount 2.873 > 2.021 Ttable and significance 0.007 < 0.05. Furthermore, leadership and organizational culture have a positive and significant influence simultaneously on employee performance as shown by the F count of 16.680 > 3.24 F table and a significance value of 0.000 < 0.05. The influence of the two independent variables including leadership and organizational culture on employee performance was 46.1%, with the other 33.9% influenced by other factors outside the research.